The Role of Satisfaction Customer To Brand Loyalty on Tokopedia - Koyongian, Yeane; Walean, Frandy (Jurnal Economic Resource, 2025)
Study This aim For analyze influence quality products and quality service to loyalty brand with satisfaction customer as variables mediation among users of the Tokopedia e-commerce platform in North Minahasa . The research method used is approach quantitative with technique data collection through online questionnaire to 208 respondents who had transactions on Tokopedia. Testing hypothesis done with using equation model structural based on Partial Least Square (PLS) with help device soft SmartPLS 3.0. Research results show that quality products and quality service influential positive and significant to satisfaction Customers . Quality the product is also proven influential positive and significant in a way direct to loyalty brand , whereas quality service No influential direct to loyalty brand . Satisfaction customer proven influential positive and significant to loyalty brand , as well as play a role as variables mediation , where satisfaction customer mediate in a way partial influence quality product to loyalty brand and mediate in a way full influence quality service to loyalty Tokopedia brand in North Minahasa . Findings This confirm importance increase quality products and services For build satisfaction in the end strengthen loyalty brand .